Bio-inspired Artificial Muscle Based on Chemical Sensors. (2017) - Ravalli, Andrea; Rossi, Claudio; Marrazza, Giovanna
Abstract: In this work, we have investigated the modeling, design and fabrication of bio-inspired artificial muscle unit capable of contracting according to the directives sent in form of chemical messengers. This new technology has the potential to revolutionize current robotics, because it could permit a paradigm shift in robots: from electro-mechanical devices to electro-chemical devices. The bio-inspired artificial muscle will be based on basic contractile units coupled to electrochemical sensors, with the purpose of allowing adaptive and flexible control similar to that in animal locomotion. An artificial nerve termination, able to modify the chemical characteristics of the inner environment, will generate directives in form of chemical messengers. Electro-chemical sensors have been used in order to detect the presence of the chemical messengers and transform them into electronic signals to be used in conventional control electronics. This study has been focused on the development and optimization of sensing materials for inorganic ions such as hydrogen ions. Among various conducting polymers studied, polyaniline (PANI) has attracted much attention due to its unique and controllable chemical and electrical properties. PANI layer has been electrochemically deposited on the gold arrays surface by cyclic voltammetry. Preliminary experiments on PANI-modified sensors in order to obtain the better sensitivity as chemical sensing used in artificial muscle unit have been carried out. To allow diffusion of chemical messages, the system has been immersed in wet environment. Using this approach, we study the effective possibility to control, assessing the performance in terms of accuracy of the control of the contraction, the impact of the delay due to the transmission time of the chemicals, precision and stability of control.